ANALISIS PEMECAHAN SAHAM (STOCK SPLIT): DAMPAKNYA TERHADAP LIKUIDITAS PERDAGANGAN SAHAM DAN PENDAPATAN PERUSAHAAN PUBLIK DI INDONESIA - Susi Dwimulyani (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2008)
This research is designed to examine the stock split in Indonesia Capital Market. We want to get empirical evidence the relationship and the effect of stock market price and frequency of stock trading to stock split actions. We also want to know the defferences of frequency of stock trading and companies operating income, before and after stock split. Research samples were selected using purposive (judgement) sampling method among listed company in Jakarta Stocks Exchange (JSX) and ninety two companies could meet as research sample, where they are the company that listed from 2000 - 2006. Afterwards this samples classified into fourty six stock splitter companies and fourty six non stock splitter companies. Before hypothesis test, normality data test using one sample Kolmogorov Smirnov test to determine whether the data were normal or not, multicolinearity test to determine whether discovered relationship among independent variables and outocorelation test to examine the correlation error between period. The hypothesis test are tested using the logistic regression to see weather the stock market price and frequency of stock trading have significant influence to the stock split, and using the paired sample t test to compare the fourty six stock splitter companies have the increasing frequency of stock trading and operating income, before and after stock split. The result of the logistic regression showed that stock market price influence stock split but the frequency of stock trading did not. The result of paired t-test showed that there had no increasing frequency of stock trading and operating income before and after stock split.